Pengaruh Harga Jual Terhadap Permintaan Telur Ayam Menggunakan Pendekatan Regresi Studi Kasus: Agen Telur ABC - Husen Santosa, Sesar; Prayudha Hidayat, Agung; Siskandar, Ridwan; Rizkiriani, Annisa (Jurnal Sains Indonesia, 2021)
ABC Egg Agents ability to develop its business activities cannot be separated from the purchasing power of consumers to buy eggs of the appropriate quality and quantity. In the business of selling chicken eggs, the factors that can increase profit are eggs' selling price. One of the reasons for fluctuating sales conditions at egg agents is the selling price is too high, resulting in a decline in sales. The results of hypothesis testing show the acceptance of Hypothesis one, which offers a relationship between the selling price and the demand for eggs. Increasing selling prices can affect the market because the value of determination (R2) is above 80%, which is 91.7% which describes a solid negative relationship. This condition shows that if the price increases, the demand will decrease. This condition indicates that the Egg Agent must manage the selling price properly to increase the demand.